Local knowledge for sustainable development: a pragmatic view. (2017) - Quartey, Samuel Howard; Wells, Sam
A complete understanding of sustainable development is inconceivable without discovering the pragmatic nature of the local knowledge embedded within industries. To fully understand the role of industries in sustainable development, it is particularly important to incorporate two underdeveloped perspectives: local knowledge from industries as a major determinant of sustainable development; and pragmatism as an underlying tool for developing this knowledge. This paper provides a pragmatic view of local knowledge towards an understanding of sustainable development. Pragmatism as an analytical perspective was examined. The major themes of pragmatism were identified and critiqued. The literature on local knowledge and sustainable development were also reviewed and synthesised. The synthesis of the literature suggests that through reflexivity, social processes and continuous experimentation, industries can develop a pragmatic local knowledge which informs their actions, practices and interventions towards sustainable development. A conceptual framework with relevant research propositions has been proposed for future empirical investigation. The novelty of this framework lies in its ability to show how industries can practically and actively support sustainable development with their pragmatic local knowledge.